Rare compound heterozygous variants in PNKP identified by whole exome sequencing in a German patient with ataxia-oculomotor apraxia 4 and pilocytic astrocytoma - Scholz, Christian; Golas, M. M.; Weber, R. G.; Hartmann, C.; Lehmann, U.; Sahm, Felix; Schmidt, G.; Auber, B.; Sturm, M.; Schlegelberger, B.; Illig, T.; Steinemann, D.; et al. (Clinical genetics, 2018)
Ataxia-oculomotor apraxia type 4 (AOA4) is a rare autosomal recessive neurologic disorder. The phenotype is characterized by ataxia, oculomotor apraxia, peripheral neuropathy and dystonia. AOA4 is caused by biallelic pathogenic variants in the PNKP gene encoding a polynucleotide kinase 3′-phosphatase with an important function in DNA-damage repair. By whole exome sequencing, we identified 2 variants within the PNKP gene in a 27-year-old German woman with a clinical AOA phenotype combined with a cerebellar pilocytic astrocytoma diagnosed at 23 years of age. One variant, a duplication in exon 14 resulting in the frameshift c.1253_1269dup p.(Thr424fs*49), has previously been described as pathogenic, for example, in cases of AOA4. The second variant, representing a nonsense mutation in exon 17, c.1545C>G p.(Tyr515*), has not yet been described and is predicted to cause a loss of the 7 C-terminal amino acids. This is the first description of AOA4 in a patient with central European descent. Furthermore, the occurrence of a pilocytic astrocytoma has not been described before in an AOA4 patient. Our data demonstrate compound heterozygous PNKP germline variants in a German patient with AOA4 and provide evidence for a possible link with tumor predisposition. Localization of the 2 variants in human PNKP NP_009185.2. NM_007254.3:c.1253_1269dup p.(Thr424fs*49) is predicted to cause a frameshift within the kinase domain, NM_007254.3:c.1545C>G p.(Tyr515*) is predicted to cause loss of 2 C-terminal amino acids of the kinase domain and 5 additional C-terminal amino acids.
Gesehen am 22.04.2020